The effects of different thermal treatments on amino acid contents and chemometric-based identification of overheated honey - Zhao, Haoan; Cheng, Ni; Zhang, Ying; Sun, Zheng; Zhou, Wenqi; Wang, Yin; Cao, Wei (Food science & technology, 2018)
This study was dedicated to distinguish overheated honey under simulated industrial thermal treatment by analyzing the amino acid contents. In this research, jujube honey and chaste honey samples were characterized by amino acids contents, color values and 5-hydroxymethylfurfural (5-HMF) contents after different thermal treatments. According to the results and multivariate statistical analysis, the contents of most amino acids in honey decreased after heat treatment, and there were significant differences between moderate and over processed honey samples. It also turns out that the sensitive markers of thermal treating are 5-HMF, b*, L*, a* and proline in jujube honey, 5-HMF, L*, b*, a* and phenylalanine in chaste honey. The above researches indicate that all honey samples in present study should be subject to category division of whether overheating. [Display omitted] •The effects of thermal treatments on 16 kinds of amino acids in honey was clarified.•Amino acid profiles could distinguish the overheated honey.•Multivariate statistical analysis was used to identify overheated samples.